Stage‐Dependent Inhibitory Connectivity in Striatal‐Motor Circuit in Huntington's Disease - Yinghua Jing; Imis Dogan; Rena Theda Overbeck; Kathrin Reetz; Sandro Romanzetti (Annals of Clinical and Translational Neurology)
ABSTRACT Background Elucidating dysfunctional connectivity patterns among key brain regions in Huntington's disease (HD) underlying progression may have implications for developing treatment and therapeutic evaluation. Objective Explore the relationship between abnormal spontaneous resting‐state activity and atrophy in HD‐specific brain regions and clarify effective connectivity changes among them across different stages of HD. Methods Amplitude of low‐frequency fluctuation (ALFF) analysis was used to detect abnormal spontaneous neural activity; voxel‐based morphometry analysis was applied to assess atrophy; spectral dynamic causal model (DCM) was conducted to estimate regional effective connectivity between HD participants and healthy controls, as well as between preclinical mutation carriers and symptomatic patients. Results Voxel‐wise whole‐brain ALFF analysis identified the bilateral caudate nucleus, putamen, and motor cortex as HD‐specific brain regions. ALFF changes in the caudate nucleus and putamen correlated with their respective volumetric atrophy, whereas ALFF changes in the motor cortex preceded its atrophy in the HD preclinical stage. Subsequently, DCM revealed increased inhibitory connectivity from the bilateral caudate nucleus to the motor cortex in HD participants compared to controls. Moreover, compared to preclinical mutation carriers, symptomatic patients showed decreased inhibitory connectivity from the right putamen to the bilateral caudate nucleus, with nonlinear relationships with motor scores. Conclusions Our results indicate that striatal atrophy and hyper‐inhibition of caudate‐motorial connectivity might contribute to the regional function alterations in HD. Furthermore, disruption of inhibitory connectivity in the striatal‐motor circuit may play an important role in the emergence of motor symptoms.